Uma discussão do conceito de pulsão de morte a partir das contribuições de Freud e Ferenczi - Bissoli, Sidney da Silva Pereira (Universidade Federal de São Carlos, 2008)
The present dissertation intends to discuss the concept of death s drive in the works of Freud and Ferenczi. Figueiredo (1999) debated similar subject, as he examined Beyond the pleasure principle (FREUD, 192) and Thalassa (FERENCZI, 1924), through a rereading of Freudian s text of 1920, approaching both psychoanalysts in relation to death s drive notion, stressing the regressive character, not of a instinctual group, but of the own organism. The present essay, nevertheless, focuses the uneasy conciliation between Freud and Ferenczi in this point, leading the last, at his final thoughts, to emphasize formally his difference in relation to Freud.
Keywords: Freud, Sigmund, 1856-1939; Ferenczi, Sándor, 1873-1933; Psicanálise e filosofia; Psicanálise; CIENCIAS HUMANAS::FILOSOFIA